366 MISUSE OF CHILD RESTRAINT SEATS IN MANITOBA: RESULTS OF A 2004 SURVEY. Issue 1 (1st January 2007) - Blair, J.; Perdios, A.; Babul, S.; Cripton, P.; Pike, I.; Mulpuri, K.; Desapriya, E.
Abstract : Introduction: Child passenger restraints, including rear-facing infant seats, forward-facing toddler seats, and booster seats, provide protection for pediatric passengers traveling in motor vehicles. Objective: To investigate the use and misuse rate of child restraint seats in Manitoba. Methods: Characteristics of child restraint seat use were assessed at 10 child safety seat inspection surveys held between May 2004 and August 2004 in Manitoba. The sample of convenience included (1) rear-facing infant seat: for infants until they are at least 20 pounds and 1 year old ( n = 49); (2) forward-facing toddler seat: for toddlers 20 to 40 pounds and 1 to 4 years old ( n = 175); and (3) booster seats: for children 40 to 80 pounds and 4 to 8 years old ( n = 118). In all, MCSC child safety seats specialists inspected a total of 342 child restraint seats. Results: The overall rate of misuse was 63%, with 73% of infant carriers used inappropriately. The most common type of misuse found in infant carriers was loosely fitted seats (91%) followed by chest clips in the wrong position (86%). Seventy-four percent of forward-facing seats were incorrectly used. The most common type of misuse found in forward-facing child restraints was harness straps placed through the wrong slot (95%) followed by seats too loosely fitted (66%). Forty-three percent of booster seats were used incorrectly. The most common misuse found in booster seat was no head and neck protection offered (46%) followed by seat belts not crossing the child's chest over the shoulder (37%). The risks of misuse of infant carriers compared with booster seats were nearly four times higher (odds ratio 3.63; confidence interval 1.75-7.55). The risks of misuse of forward-facing child restraint seats compared with booster seats were also nearly four times higher (odds ratio 3.68; confidence interval 2.24-6.04). Conclusions: This paper is the first to describe child restraint seat misuse in Manitoba following the 1997 child restraint use survey conducted by Transport Canada. Infant carriers and forward-facing child restraint seats were much more likely to be misused than booster seats. This study also identified a statistically significant higher rate of infant carrier and forward-facing child restraint misuse compared with booster seat misuse in Manitoba. The Manitoba child restraint seat survey suggests that a large number of children still remain poorly protected when traveling in motor vehicles. The survey data presented here can be used to inform parents about the importance of correct child restraint use.